EFFECT OF COMBUSTIBLE CONTENT IN COAL ASH REFUSE ON THE EFFICIENCY OF THERMAL OIL HEATER SYSTEM - HAIFA WAHYU (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2012)
This paper provides an analysis on the effect of combustible content in coal ash refuse the efficiency towards combustion and heat thermal oil heater system in a coal furnace that had been studied. The study investigated the discrepancy of the actual performance of the heater compared to that as stated in the design specification. The study assumed that coal type and operational problem were the cause of deviation. Both affect combustion efficiency and the amount of reactive materials within coal ash refuse. Combustible content within the coal ash refuse was the used as the source data. Using indirect method, the amount of losses can be determined from the amount of combustibles in the coal ash refuse. The work involved measuring the temperature of oil and flue gas, analyzing the ash content and calculating the losses based on two sets of operational data. System efficiency and heat exchanger rating were calculated by reducing the amount of total losses from the full design capacity. If the reactive composition within the coal ash in combustible content, the amount of coal consumption is higher in order to attain the heat desired capacity for heating. Such a contition is caused by decreasing the energy capacity and reducing the furnace effectiveness